2023
DOI: 10.1186/s12873-023-00830-w
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making on the fly: a qualitative study of physicians in out-of-hospital emergency medical services

Ema Karmelić,
Henrik Lindlöf,
Jamie Linnea Luckhaus
et al.

Abstract: Background Out-of-hospital Emergency Medical Services (OHEMS) require fast and accurate assessment of patients and efficient clinical judgment in the face of uncertainty and ambiguity. Guidelines and protocols can support staff in these situations, but there is significant variability in their use. Therefore, the aim of this study was to increase our understanding of physician decision-making in OHEMS, in particular, to characterize the types of decisions made and to explore potential facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Clinical measures and the patient's medical history are two important clinical elements that the emergency physician considers when making decisions in hospital emergencies [10]. A comprehensive understanding of the patient's medical history allows physicians to properly customize their treatment plans.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Clinical measures and the patient's medical history are two important clinical elements that the emergency physician considers when making decisions in hospital emergencies [10]. A comprehensive understanding of the patient's medical history allows physicians to properly customize their treatment plans.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Several studies and reviews have reported correlations between decision fatigue and clinical outcomes or decision quality in emergency medicine. These investigations provide quantitative data that suggests potential links between the mental strain associated with decision-making and its impact on healthcare providers and patients [27][28][29][30][31][32][33].…”
Section: Studies Showing Correlationsmentioning
confidence: 99%